EFEKTIVITAS PROGRAM KESELAMATAN DAN KESEHATAN KERJA (K3) – STUDI LITERATUR - Tanti Winarti, Banowati Talim (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2017)
This paper examines how important occupational safety and health (OSH) programs are in companies regardless of size. This study uses literature studies by collecting various related journal OSH companies. The results of this review indicate that the effectiveness of the OSH program is inseparable from the role of committed leaders and employee participation. Some studies place the PDCA Cycle as a means of maintaining and reviewing OHS programs in an effort to continually improve OSH program. Regular maintenance and reviews help the company to evaluate the effectiveness and consistency of the OSH program for the company's policies, objectives and goals. The effectiveness of the OSH program can also be measured through OSH audit, to see whether the company's OSH program standards and guidelines currently used or implemented can be effective or adequate in controlling the danger of workplace accidents. Effective management of OSH programs can reduce the potential for workplace accidents and reduce the cost of workplace accidents. It can also reduce conflict, encourage better working relationships, improve corporate image, increase motivation, reduces absenteeism, and increase company productivity and performance as competitive advantages. The implementation of the OSH program must be supported by relevant company policies, so that the OSH program can run effectively.Â Keywords: Effectiveness of the OSH Program; PDCA Cycle; OSH Audit; Policies.